MANAJEMEN PEMBELAJARAN BLENDED LEARNING DALAM UPAYA MENINGKATKAN EFEKTIVITAS BELAJAR MAHASISWA - HAPUDIN, MUHAMMAD SOLEH (Unversitas Katolik Santo Thomas, 2020)
The development of the 21st century world is marked by the use of information and communication technology in all facets of life. Utilization of Information Communication and Technology (ICT) through the internet in all fields, including in the education or learning process. Progress in the world of ICT changes many things, in the world of work that can be replaced by advances in the world of Internet technology of Thing (IoT) and Artificial Intelligence (AI). Lecturers must have the ability to adapt to changes and technological development by changing the learning process so far the lecture is not only face-to-face, but can be done online in order to improve education access services. Internet as a result of technological developments certainly has an influence in the world of education, especially in the learning process that has changed conventional learning patterns into modern patterns based online with the use of Information Communication and Technology (ICT), known as E-Learning.Â Collaborative learning between conventional learning and ICT-based learning developed as collaborative learning or known as Blended Learning. In the management of Blended Learning learning is very effective, Blended Learning Learning is very effective to use because it provides easy accessibility of students wherever, whenever and wherever can be accessed in accordance with the required learning outcomes. Blended Learning learning resources are not fixated on lecturers in the course but can be from various sources, in the form of digital, video and other sources of information.